2009
DOI: 10.1371/journal.pbio.1000174
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Functional Eyes from Pluripotent Cells

Abstract: The directed differentiation of pluripotent cells into specific cell-types is a major hurdle in regenerative medicine. This study shows the eye field transcription factor factors can direct pluripotent cells into functioning frog eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 37 publications
(46 reference statements)
6
63
0
1
Order By: Relevance
“…The overexpression of high levels of noggin 1 activates Nodal/TGFb and Shh pathways in ACES cells eliciting a retinal fate in vitro, and these cells are able to induce the formation of a normal eye after transplantation in the eye field region (Lan et al, 2009;Messina et al, 2015). Similar results were obtained treating ACES cells with Noggin protein (Viczian et al, 2009). Moreover, noggin shows a conserved expression in the adult retina of different vertebrates (Messina et al, 2014).…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…The overexpression of high levels of noggin 1 activates Nodal/TGFb and Shh pathways in ACES cells eliciting a retinal fate in vitro, and these cells are able to induce the formation of a normal eye after transplantation in the eye field region (Lan et al, 2009;Messina et al, 2015). Similar results were obtained treating ACES cells with Noggin protein (Viczian et al, 2009). Moreover, noggin shows a conserved expression in the adult retina of different vertebrates (Messina et al, 2014).…”
Section: Introductionsupporting
confidence: 56%
“…Previous studies have analysed noggin 1 role starting from the initial phases of Xenopus development (Smith and Harland, 1992;Bayramov et al, 2011) or in ex-vivo experiments using animal cap explants (Zuber et al, 2003;Lan et al, 2009;Viczian et al;2009;Wong et al, 2015;Messina et al, 2015). No data are reported for a possible role of noggin 1 in later stages of eye development in vivo, however.…”
Section: Overexpression Of Noggin 1 In the Optic Vesiclementioning
confidence: 99%
See 1 more Smart Citation
“…In Xenopus, Noggintreated pluripotent cells were found to be able to differentiate into a multipotent retinal progenitor lineage, which facilitated functional eye formation following transplantation in vivo [26]. colleagues also reported that a high-dose treatment of Noggin promoted retinal cell differentiation in Xenopus embryonic stem cells [27].…”
Section: Noggin Promotes the Differentiation Of Opa1 +/− -Ipscs Into mentioning
confidence: 99%
“…Bien que ces travaux montrent qu'il est possible d'induire in vitro des neurones de rétine, les conditions n'étaient pas réunies pour forcer ces cellules à s'organiser en une structure épithéliale. En revanche, des progéniteurs rétiniens issus de la différen-ciation de CSE puis réimplantés dans un embryon de grenouille, sur ses flancs par exemple, s'agencent spontanément pour former des rétines ectopiques [6]. Une étape était franchie, mais d'autres défis restaient à relever pour réaliser le rêve de certains de former de toute pièce un oeil ex vivo.…”
Section: Comment Se Forme Un Oeil ?unclassified